191k views
3 votes
Bet u can’t solve this

Bet u can’t solve this-example-1
User Chklang
by
4.1k points

1 Answer

3 votes

Answer:

Explanation:

Assuming you're solving for p:


m=2^(-1) *2^p(2^p-1)

Let
y=2^p

Now we can re-write the equation with
y instead of
2^p.


m=(1)/(2) y(y-1)


2m=y^2-y


y^2-y-2m=0

Use the quadratic formula to get:


y = (1+√(1+8m) )/(2)

or


y = (1-√(1+8m) )/(2)

Therefore, using natural log and log rules:


2^p = (1+√(1+8m) )/(2),
ln(2^p)= ln((1+√(1+8m) )/(2)),
pln(2) = ln((1+√(1+8m) )/(2)),
p = (ln((1+√(1+8m) )/(2)))/(ln(2))

or


2^p = (1-√(1+8m) )/(2),
ln(2^p)= ln((1-√(1+8m) )/(2)),
pln(2) = ln((1-√(1+8m) )/(2)),
p = (ln((1-√(1+8m) )/(2)))/(ln(2))

If I haven't made any mistakes this should be correct!

User Ankit Bhardwaj
by
5.6k points